2009
DOI: 10.1088/1748-0221/4/07/p07010
|View full text |Cite
|
Sign up to set email alerts
|

The radiation tolerance of specific optical fibres exposed to 650 kGy(Si) of ionizing radiation

Abstract: The radiation tolerance of specific optical fibres exposed to 650 kGy(Si) of ionizing radiation To cite this article: B Arvidsson et al 2009 JINST 4 P07010 View the article online for updates and enhancements. Recent citations Gary Pickrell et al -JTAG-based remote configuration of FPGAs over optical fibers B. Deng et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…A number of fibres were tested at warm temperatures (up to 70 • C) to doses in excess of 500 kGy(Si), and were found to perform well [6]. For example, the radiation induced attenuation expected for a realistic route through the ATLAS detector was found to be 0.14 dB for Corning SMF-28e.…”
Section: Previous Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of fibres were tested at warm temperatures (up to 70 • C) to doses in excess of 500 kGy(Si), and were found to perform well [6]. For example, the radiation induced attenuation expected for a realistic route through the ATLAS detector was found to be 0.14 dB for Corning SMF-28e.…”
Section: Previous Resultsmentioning
confidence: 99%
“…However, these tests were performed at a dose rate of 27 kGy(Si)/hr, orders of magnitude higher than that expected at the HL-LHC. Research has shown that RIA is strongly dependent upon dose rate [5,6], and so the other fibres could not be excluded from use. This paper describes tests performed at low temperatures (between -24 • C and -30 • C) and at a comparatively low dose rate of 0.7 kGy(Si)/hr.…”
Section: Previous Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RIA is affected by: 1. the manufacturing conditions, the parameters related to the technology used in producing the optical fiber: the deposition conditions, the draw process characteristicsdraw speed, fiber drawing tension, the preform deposition temperature, oxygen-toreagent ratio (02/R) used during core and clad deposition (Friebele, 1991;Girard et al, 2006;Hanafusa et al, 1986); 2. the existence, prior to the irradiation, of some precursors (Miniscalco et al, 1986); 3. the dopants present in the optical fiber core or cladding (pure silica, or doped with Ce, Er, Ge, F, N, P, Yb, high-OH, low-OH, high-Cl, low-Cl, H2-loading), (Arvidsson et al, 2009;Berghmans, 2006;Berghmans et al, 2008;Bisutti et al, 2007;Brichard & Fernandez Fernandez, 2005;Friebele, 1991;Girard et al, 2004a;Girard et al, 2004b;Girard et al, 2008;Griscom et al, 1996;Henschel et al, 1992;Kuyt et al, 2006;Lu et al, 1999;Mady et al, 2010;Paul et al, 2009;Regnier et al, 2007;Vedda et al, 2004;Wijnands et al, 2007), in some situations such ingredients contribute to the radiation hardening (Brichard et al, 2004;Brichard & Fernandez Fernandez, 2005;Girard et al, 2009); 4. the residual substances remaining after the manufacturing process, as for example chlorine having an associated color center in the UV spectral range, which can extend into the visible Girard & Marcandella, 2010); 5. the type of radiation to which the optical fiber is subjected (Arvidsson et al, 2009;Bisutti et al, 2007;Brichard et al, 2001;Calderón et al, 2006;Girard et al, 2004a;Girard et al, 2004b;…”
Section: Optical Fibers Performances Under Irradiationmentioning
confidence: 99%